Definição e uso dos termos fábula e fabuloso em textos metalinguísticos no século XVIII - Silvestre, João Paulo (2005)
18th-century metalinguistic texts illustrate the usage of the words fable and fabulous in contexts not pertaining to the reflection on literary genres. In textsdescribing customs, myths, religious practice and wondrous events, classifying any discourse as fabulous could convey judgements of value justified by a reaction inopposition to heterodoxy.